In the Steps of Operetta: Austrian Cinema’s Relation to History - Bono, Francesco (European Journal of Multidisciplinary Studies, 2019)
This essay intends to investigate some aspects of the multifaceted relationship between the Viennese operetta and Austrian film in the period from the 1930s to the 1950s. In particular, the essay will try to trace the influence of the operetta on the way in which Austrian films depicted the country’s history. Focusing on some of the most popular Austrian films of the period, including Willi Forst’s Operette (1940), Wiener Blut (1942) and Wiener Mädeln (1944-49), as well as Ernst Marischka’s trilogy from the late 1950s about the Austrian empress “Sissi”, the essay will critically discuss Austrian cinema’s penchant for the past, investigating the affinity of the Austrian (musical) film to the Viennese operetta, which served as its ideological and aesthetic model. In its affection for the past, Austrian cinema followed in the steps of the Viennese operetta. In contrast with the Hollywood musical genre or German musical films like Die Drei von der Tankstelle (1930) or Hallo Janine (1939), to mention just two of the most famous ones from the pre-war era, history was a key component of the Austrian Musikfilm. In Austria, the musical film overlapped with the historical genre, and it strongly influenced the country’s memory of its past. By investigating the connection between the Viennese operetta and Austrian cinema, this essay aims to provide a better understanding of Austrian films in the cultural, political and historical context in which they saw the light of day.
Keywords: : Austrian cinema, Austrian culture, Operetta, Musical film.